Effects of foliar spray of Boron Nanoparticles and Tillage system on production Medical active substances and chemical structure in Alfalfa (Medicago sativa L. ) - Mohmmed Swadi Zagher Al rkabe1 (University of Thi-Qar Journal of agricultural research, 2024)
Field experiment conducted at two summer season 2020-2021 and 2021-2022 on clay sandy soil in Al-Diwanyia. The experiment was design as Complete Randomized Block Design with three replications arranged for split-pilot design, and Least Significant differences 0.05 the main treatment contend two level of Tillage system ( 10, 25)cm within their four levels of Boron Nanoparticles (BNPs)( 0 , 10 , 20 , 30) mg.l-1. and irrigated every 3 days I took sample of soil before planting to analysis it and to learn physical and chemical properties table 1. Alfalfa Seeds sowing at rate 20 kg.ha-1(1 cm depth) at 1/4, after 7 months I took a samples to measure . The results showed all factors and interactions were significant effect and produce three medical active substances Oxalic acid , Methypyridazin, Benzaldehyde and protein , carbohydrates ,Fats , total chlorophyll , forage yield and their max values respectively(2.67 , 2.5 , 2.58 , (21.41 , 5.5 , 1.02)% , 2.7 mg. 2g-1 , 1.79 T,ha-1) in interaction 25 cm and 30 mg.l-1 while the min values respectively ( 0.02 , 0.02 , 0.02 , (18.8 , 4.83 , 0.78)% , 2.38 mg.2g-1 and 1.33 T.ha-1) in the interaction of 0 kg.ha-1 and 0 mg. l-1 BNPs .